Desain Didaktis Bahan Ajar Matematika SMP Berbasis Learning Obstacle dan Learning Trajectory - Endang Dedy; Encum Sumiaty (JRPM (Jurnal Review Pembelajaran Matematika), 2017)
This study is to correct mathematical learning by didactic design based on learning obstacles and learning trajectory. This is a qualitative study through Didactical Design Research (DDR) by three analytical phase, i.e. 1) didactical situation analysis before learning presented as didactical design hypothesis including ADP; 2) metapedadidactical analysis which analyzes teacher’s ability such as unity, flexibility, and coherency in learning; 3) retrospective analysis which is the correlated analysis between the result of didactical situation hypothesis analysis and metapedadidactical analysis. The result of problem analysis related to integer arithmetic operation, a concept of function, and two triangle similarity concept, implementation of early didactical design could predict probable mistakes done by students and even if the mistakes still there, it was decreased compared to early learning obstacle test. These conditions were reinforced after learning with mathematics score school succeed standard 75% was done.